2018
DOI: 10.3390/met8050300
|View full text |Cite
|
Sign up to set email alerts
|

Laser Powder Bed Fusion of a High Strength Al-Si-Zn-Mg-Cu Alloy

Abstract: Al-Si-Zn-Mg-Cu samples were produced using Laser Powder Bed Fusion from mixed AlSi10Mg and 7075 powders. It was observed that the introduction of silicon to an Al-Zn-Mg-Cu alloy strongly reduced the crack density, probably because of the reduction of the solidification range, the improved fluidity of the molten phase and the reduction of the coefficient of thermal expansion. The density measurements showed that crack-free samples can be successfully produced with this powder mixture. The obtained Al-Si-Zn-Mg-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…This indicates that the strength of the alloys significantly increases while their elongation decreases when the Cu content increases to 2.5%. Besides, in our study, it shows that either the Cu content or the aging treatment has little influence on the elastic modulus of aluminium alloy, which is in accordance with the results of previous studies [6,7]. Figure 10a shows the tensile curves of the four as-quenched alloys.…”
Section: Age-hardening Curvessupporting
confidence: 92%
See 1 more Smart Citation
“…This indicates that the strength of the alloys significantly increases while their elongation decreases when the Cu content increases to 2.5%. Besides, in our study, it shows that either the Cu content or the aging treatment has little influence on the elastic modulus of aluminium alloy, which is in accordance with the results of previous studies [6,7]. Figure 10a shows the tensile curves of the four as-quenched alloys.…”
Section: Age-hardening Curvessupporting
confidence: 92%
“…Cu is known to have a significant strengthening effect on Al-Mg-Si-Cu alloys [5]. Many studies [6,7] show that the strength of such an alloy can be enhanced by Cu additions as low as 0.1 wt.%. Jin et al [5] indicated that additions of 0.3 wt.% Cu increased the tensile strength of Al-Mg-Si-Cu alloys from approximately 390 to 430 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in some cases, gas atomization of specific compositions might be difficult [32]. Because of these reasons, in recent years many researchers mixed commercial powders with different chemical compositions to obtain a batch with the final required alloying elements content [32,33,34,35,36,37,38]. The phenomena that arise in the melt pool, such as the Marangoni flow and the recoil pressure effects, generally allow the distribution of the alloying elements within the melt pool [39].…”
Section: Methodologiesmentioning
confidence: 99%
“…Aversa et al [ 165 ] investigated the mechanical, metallurgical and the thermal properties for SLM of Al-Si-Zn-Mg-Cu alloy. The introduction of Si was analysed with respect to Al-Zn-Mg-Cu alloy and the crack density was found to be reduced.…”
Section: Mechanical Properties Of Slm-printed Aluminium Alloysmentioning
confidence: 99%